Regulatory changes during the Covid-19 pandemic: A comparative review of the European Union and Brazilian regulations for biological and biotechnological products - Leone Nassur, Priscila [UNESP]; Borges de Almeida, Fernanda [UNESP]; Primo, Fernando Lucas [UNESP] (Elsevier, 2025)
The process for registration of biologic products is lengthy due to the high number of studies and data required by the health authorities. However, with the COVID-19 pandemic, and the urgent need for an alternative, the authorities reduce the time for registering new products with the challenge of maintaining all the necessary reliable standards. The objective of this paper is to compare the regulatory requirements for biologics in Brazil and the European Union in the context of the pandemic and evaluate the background differences in regulations before and after the emergency. The searches were conducted in the databases of EMA and Anvisa and the results were assessed for type of document/product, regulatory scope/process step, effectiveness, and year of publication/update. Both regulators foresaw the route of registration for emergency use and followed international standards, with strict requirements for quality, safety, and efficacy. After the end of the health emergency, while EMA gradually phased out the emergency regulations, Anvisa withdrew them. It was observed that the challenges faced by the Brazilian authority and industries were related to the lack of a centralized health monitoring system. The regulators were overall aligned in the approaches during the pandemic and both had a regulatory emphasis on vaccines but the measures taken after its end differed. The main difference observed was the slower phase-out and the adoption of lessons learned strategy in the EU, which should be learning points for Anvisa if targeting a continuous readiness strategy for health emergencies.
Keywords: Biological products; Biotechnology; Covid-19; Regulatory affairs; Regulatory study